In Search of an American Catholicism: A History of Religion and Culture in Tension - Crews, Clyde Francis (Cistercian studies quarterly, 2003)
Reviews the book "In Search of an American Catholicism: A History of Religion and Culture in Tension," by Jay P. Dolan.